Impact of COVID-19 in Food Industries and potential innovations in Food Packaging to combat the pandemic – A review - Jyoti (2021)
SARS-CoV-2 (COVID-19) pandemic created worldwide havoc by infecting more than 100 million populations all over the world. Many industrial sectors were shut by the complete lockdown phase but to the contrary, food sector remained as one of the prime areas to be operational even in this pandemic period. The panic and fear of the disease generated various myths and rumors about the effects of the corona virus on raw as well as processed food materials; the associated industries like food processing and packaging severely suffered and faced huge threats due to this pandemic, affecting food safety. This article reviews the possible modes of transmission via food and attempts to highlight the innovations in food packaging that may be implemented for the safety and the quality of the food products during this COVID-19 period and future viral pandemics. This work details the precautions and safety measures employed in the food industries during this pandemic situation to create awareness and preparedness for such situations of pandemics in the future.